A Study of the Causal Relationships between GDP, Exports and FDI in Selected Countries from South East Asia and Sub-Saharan Africa from 1984-2004 - Durant, BC (2009)
Within this report is an investigation into the causality between gross domestic product (GDP), exports and foreign direct investment (FDI). Eight countries will be selected from two differing areas of the world; four from South East Asia and four from Sub-Saharan Africa. The results will then be compared on an individual and group basis.